Integral metal fiber and hollow hierarchical pore HZSM-5 molecular sieve core-shell structure catalyst as well as preparation method and application of integral metal fiber and hollow hierarchical pore HZSM-5 molecular sieve core-shell structure catalyst

By adopting a whole metal fiber@hollow multi-grade HZSM-5 molecular sieve-shell structure catalyst, the existing catalysts have low active sites in active sites and carbon accumulation are easy to block in the catalytic catalytic reactions, and they have achieved efficient efficiency Catalytic and good liquid product selectivity.

CN119368224APending Publication Date: 2025-01-28HENAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411493789.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the catalytic cracking reaction of oil and fat, existing catalysts have problems such as low utilization efficiency of active sites, easy carbon accumulation to block pores, large diffusion resistance of reactants and products, resulting in poor catalytic activity and reduced selectivity of liquid products.

Method used

Adopt a rectifier metal fiber@hollow multi-grade hole HZSM-5 molecular sieve-shell structure catalyst. Pore ​​structure and spread of circulation.

Benefits of technology

It significantly improves the catalytic efficiency and selectivity of the catalyst, effectively suppress carbon deposits, improves the selectivity of liquid products, the selectivity of hydrocarbons, and aromatics, and prolong the stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368224A_ABST
    Figure CN119368224A_ABST
Patent Text Reader

Abstract

The invention discloses a monolithic metal fiber and hollow hierarchical pore HZSM-5 molecular sieve core-shell structure catalyst as well as a preparation method and application of the monolithic metal fiber and hollow hierarchical pore HZSM-5 molecular sieve core-shell structure catalyst. The catalyst is composed of a metal fiber matrix and a hollow hierarchical pore ZSM-5 molecular sieve layer uniformly wrapping the outer surface of the fiber, and a coaxial sleeve type core-shell structure is formed. According to the catalyst, metal fibers serve as a carrier, seed crystal precoating and hydrothermal crystallization growth are carried out, and finally alkali treatment is carried out to prepare the hollow hierarchical pore structured ZSM-5 with the advantages of macropore-mesopore-micropore, adjustable pore diameter and large specific surface area. The catalyst provided by the invention can strengthen mass transfer and reduce bed pressure drop, has large specific surface area and good thermal conductivity, and can obviously improve the catalytic efficiency and selectivity of the catalyst. The catalyst is applied to a gas phase catalytic cracking reaction of vegetable fat or waste fat and has good catalytic performance, the yield of a liquid product can reach 60% or above, the total hydrocarbon content can reach 98%, the aromatic hydrocarbon content can reach 89%, and meanwhile the carbon deposition resistance is remarkable. The preparation method is simple, the structure is controllable, the method is suitable for industrial production, and the practical value and the application prospect are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation and application of a monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst for gas-phase catalytic cracking of vegetable oil or waste oil, and in particular to a fiber-structured HZSM-5 molecular sieve catalyst composed of a monolithic metal fiber substrate and a hollow multi-level pore ZSM-5 molecular sieve layer grown thereon, a preparation method thereof, and application thereof in gas-phase catalytic cracking reaction of oil, belonging to the technical field of molecular sieve catalytic materials and high-value utilization of biomass energy. Background Art

[0002] With the continuous progress of the petrochemical industry, fossil energy is frequently used as a non-renewable energy source. While it brings huge economic benefits to mankind, it also faces problems of environmental pollution and energy depletion. In order to effectively avoid a series of problems brought by petroleum energy, renewable clean energy such as biomass has received extensive attention from researchers. The main components of biomass are roughly the same as those of fossil fuels such as oil and coal, and it has the advantages of being renewable, green and clean, and carbon neutral (Curr. Opin. Chem. Biol., 2020, 59, 1-14).

[0003] The conversion of biomass such as vegetable oil or waste oil into biofuel has many advantages, such as renewable raw materials, wide sources, and almost no sulfur content in the product. At present, there are several ways to convert bio-oil into biofuel: transesterification to convert bio-oil into biodiesel; hydrogenation catalytic method to obtain biofuel by adding hydrogen to the raw materials; catalytic cracking method to obtain substances similar to petroleum products by cracking oil macromolecules at high temperature and catalyst. The catalytic cracking method is based on the thermal cracking method, which allows the heated gaseous oil molecules to be catalytically cracked by the active sites on the catalyst to obtain biofuels of different components (Bioresour. Technol., 2008, 99, 7911-7922). In the catalytic cracking process, the cracking of vegetable oils is divided into two continuous and different stages: primary cracking and secondary cracking, that is, triglycerides are first decomposed into fatty acids through free radical cracking reactions, and then fatty acids undergo a series of reactions such as cracking, deoxygenation, isomerization, aromatization, and hydrogen transfer on the catalyst surface to convert into hydrocarbons, light gaseous hydrocarbons, and heavy hydrocarbons (Energ. Conv. Manage., 2007, 48, 2386-2398). In addition, the catalytic cracking method for producing biofuels has the advantages of simple equipment, low production cost, flexible operation, and easy discretization, so it has broad application prospects.

[0004] Among the many catalysts for converting vegetable oil raw materials into chemicals and biofuels, molecular sieve catalysts have high adsorption capacity, unique pore structure and ion exchange performance, and are therefore widely used in catalytic cracking of oils and fats. Adding molecular sieve catalysts to the traditional catalytic cracking process can increase the production of aromatics, and the shape selectivity of molecular sieves also enables them to be used in a variety of catalytic reactions. Common molecular sieve catalysts include HZSM-5, SBA-15, Beta, MCM-41, HZSM-11, etc. Among these molecular sieve catalysts, HZSM-5 catalyst has a better acid site distribution and shape selectivity, which can bring higher olefin and aromatic yields in the application of oil conversion into biofuels, and is the most widely used.

[0005] In the process of catalytic cracking of oil and fat, the transfer rate of large oil molecules into the microporous channels of ZSM-5 is low, and it is easy to block the channels with carbon deposition, and the utilization efficiency of active sites in the channels is low, resulting in poor catalytic activity of molecular sieves. In addition, the diffusion resistance of reactants and products in the channels is large, which causes excessive cracking due to their long residence time, thereby reducing the selectivity of liquid products and accelerating the deactivation of catalyst carbon deposition (Sci.Total.Environ.,2018,631-632,1611-1622). Chaihad synthesized hollow HZSM-5 with mesopores by alkaline hydrothermal treatment. The mesoporosity and acidity increased after alkali treatment, and it was applied to the catalytic cracking of lignin. There are more light olefins in the product, and its effect is better than that of HZSM-5 with microporous structure (Bioresour.Technol.,2021,341,125874). Therefore, many researchers have improved the HZSM-5 molecular sieve by preparing multi-level pores in various ways to increase its mass transfer rate and accessibility of active sites.

[0006] In order to minimize the effect of the catalyst on the reaction rate and the effect of the diffusion of reactants and products, the particle size of the catalyst is relatively small. However, if the catalyst particle size is too small, it will cause problems such as low reactant transfer efficiency, excessive pressure drop, increased energy consumption, or the catalyst is mixed in the product and difficult to separate (Appl. Catal. A: Gen., 2018, 562, 234-240). This is an irreconcilable contradiction for the fixed bed reactor composed of particle catalysts. Deng et al. prepared SS-fiber@HZSM-5 molecular sieve catalyst for esterification of acetic acid and ethanol, thereby avoiding the problems of internal diffusion limitation and high mass transfer resistance caused by the use of traditional HZSM-5 powder catalysts, and effectively improving the stability of the catalyst (J. Chem. Technol. Biotechnol., 2017, 93, 827-841). Therefore, structural design of the catalyst can effectively avoid problems such as channel flow and particle agglomeration during the reaction process, and can significantly optimize the fluid mechanics behavior and heat and mass transfer performance of the catalyst bed.

[0007] Currently, monolithic structured catalysts and reactor technologies have been widely proven to significantly optimize the fluid mechanics behavior and heat and mass transfer performance of the catalyst bed. Catalysts with multi-level pore structures can regulate the pore structure of the catalyst itself, which is beneficial to inhibiting the carbon deposition of the catalyst. Structured multi-level pore catalysts show high flexibility in regulating diffusion distance and porosity, thereby significantly improving the reaction efficiency. Therefore, it is expected that structured multi-level pore HZSM-5 catalysts will improve catalytic activity, stability, and selectivity of target products. However, there are technical difficulties in the structured preparation of multi-level pore HZSM-5 catalysts. The selection of metal substrates, the regulation of alkali treatment conditions, and the effective loading of molecular sieves all require further design and verification. Summary of the invention

[0008] In view of the above problems existing in the prior art, the present invention provides a monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst with good selectivity, high stability and resistance to carbon deposition, as well as a preparation method and application thereof, so as to improve the selectivity, deoxygenation degree, yield and anti-carbon deposition stability of liquid hydrocarbons in the catalytic cracking reaction of oils and fats.

[0009] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0010] The monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst for gas-phase catalytic cracking of vegetable oil or waste oil described in the present invention is composed of a monolithic metal fiber matrix and a ZSM-5 molecular sieve layer with an internal hollow, multi-level pore structure, wherein the monolithic metal fiber matrix is ​​the inner core and the hollow multi-level pore HZSM-5 molecular sieve is the sleeve, forming a three-dimensional network structure composed of a plurality of coaxial sleeve-type core-shell structures.

[0011] As a preferred solution, the metal fiber is copper fiber, nickel fiber, stainless steel fiber or titanium fiber.

[0012] As a further preferred embodiment, the diameter of each metal fiber is 2-50 μm.

[0013] As a preferred solution, the hollow multi-level pore HZSM-5 molecular sieve is a silicon-aluminum molecular sieve with a Si / Al molar ratio of 2 to 500 or a pure silicon molecular sieve without aluminum.

[0014] As a further preferred embodiment, the mass percentage of the hollow multi-level pore ZSM-5 molecular sieve in the monolithic catalyst is 2 to 30%.

[0015] As a further preferred embodiment, the hollow multi-level pore ZSM-5 molecular sieve has a pore size of 50 to 800 nm, the multi-level pores include macropores, mesopores and micropores, the macropore porosity is 60 to 95%, the mesopore pore size is adjustable between 2 and 100 nm, the micropores come from the ZSM-5 molecular sieve (<2 nm), and the specific surface area is 20 to 100 m 2 g -1 .

[0016] The present invention also provides a method for producing the metal fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst, comprising the following steps:

[0017] a) using a monolithic metal fiber sheet as a substrate, firstly performing a surface pretreatment on the monolithic metal fiber sheet, then immersing the monolithic metal fiber sheet in a suspension aqueous solution composed of nano ZSM-1 seed crystals, taking the monolithic metal fiber sheet out and drying it after immersion for a certain period of time, thereby obtaining a monolithic metal fiber substrate pre-coated with nano molecular sieve seed crystals;

[0018] b) placing the monolithic metal fiber substrate pre-coated with nano ZSM-5 seed crystals into a molecular sieve crystallization solution for hydrothermal crystallization growth, and calcining the obtained structured molecular sieve at a certain temperature for a certain time;

[0019] c) adding the structured molecular sieve into an alkaline solution for secondary hydrothermal crystallization or water bath stirring;

[0020] d) The prepared structured hollow multi-level pore molecular sieve is subjected to NH 4 Cl solution ion exchange to obtain H-type molecular sieve, which is then calcined.

[0021] As a preferred solution, in step a), the surface pretreatment of the monolithic metal fiber matrix is ​​performed as follows: the monolithic metal fiber sheet is placed in acetone, ultrasonicated for 5 to 30 minutes, placed in an oven at 40 to 100°C for drying, and calcined at 200 to 500°C for 1 to 5 hours. The purpose of the pretreatment is to use high temperature treatment to produce an oxide layer on the metal matrix, so as to ensure that the molecular sieve maintains good bonding strength with the metal matrix in the subsequent alkaline solution treatment.

[0022] As a preferred embodiment, in the suspended aqueous solution in step a), the mass percentage of nano ZSM-5 seeds is 1% to 5%, the nano ZSM-5 seeds are pure silicon molecular sieves or silicon aluminum molecular sieves with a Si / Al molar ratio of 20 to 500, the immersion time is 2 to 24 hours, and the drying conditions are 100°C for 6 to 12 hours.

[0023] As a preferred embodiment, the molecular sieve crystallization solution in step b) is composed of tetraethyl orthosilicate (TEOS), tetrapropylammonium hydroxide (TPAOH), aluminum nitrate nonahydrate [Al(NO 3 ) 3 9H 2 O], sodium hydroxide (NaOH) and deionized water in a molar ratio of TEOS:TPAOH:[Al(NO 3 ) 3 9H 2 O]:NaOH:H 2 O=130:(14~50):(0.5~5):(5~13):(20~1000).

[0024] As a preferred embodiment, the conditions for hydrothermal crystallization growth in step b) and step c) are as follows: static crystallization at 90-180° C. for 6-72 hours,

[0025] As a preferred embodiment, the calcination conditions in step b) and step d) are as follows: calcination in an air atmosphere at 500-600° C. for 5-6 hours.

[0026] As a preferred embodiment, the concentration of the alkaline solution in step c) is 0.01-2 mol / L, and the heating and stirring conditions are 20-80° C. and stirred for 10-120 min. The composition of the alkaline solution includes NaOH, TPAOH, NaHCO 3 、Na 2 CO 3 One or more of the above, more preferably TPAOH.

[0027] As a preferred embodiment, the conditions for ion exchange in step d) are as follows: ion exchange at 60-90°C for 1-12h, NH 4The concentration of Cl solution is 0.1~2mol / L.

[0028] The present invention also provides the use of the monolithic metal fiber @ hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst in the gas phase catalytic cracking of vegetable oil or waste oil, characterized in that the monolithic metal fiber @ hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst is used as a catalyst in the gas phase catalytic cracking process of vegetable oil or waste oil, and has good aromatic selectivity and anti-carbon deposition performance, and the method is as follows:

[0029] a) The monolithic metal fiber@hollow multi-level pore HZSM-5 core-shell structure catalyst is loaded into a quartz tube of a tubular reactor, wherein the mass of the molecular sieve in the catalyst is 1 g; nitrogen gas at a certain flow rate is continuously introduced into the tube as a carrier gas to avoid side reactions between oxygen and grease under high temperature conditions.

[0030] b) The quartz cracking tube is heated by a two-stage tubular heating furnace, with the temperature of the first stage set at 300-450°C to fully preheat and gasify the oil; the temperature of the second stage is set according to the specific reaction temperature, ranging from 380-550°C.

[0031] c) The oil enters the quartz cracking tube at a certain flow rate through a peristaltic pump, and after preheating and vaporization, a continuous catalytic cracking reaction occurs; the mass space velocity of the oil is 1 to 15 h -1 , the gaseous and liquid products are collected by a gas collecting device and a liquid collecting device respectively for analysis.

[0032] As a preferred solution, the catalyst silicon-aluminum ratio is 100, the nitrogen flow rate is 20 mL·min-1, the mass space velocity of oil and fat is 4h-1, and the liquid product yield is more than 60%, wherein the hydrocarbon content in the liquid product is as high as 98%, and the aromatic content is as high as 89%.

[0033] As a further preferred embodiment, the oil comprises non-edible vegetable oils such as castor oil, palm oil, cottonseed oil, etc., acidified oil or waste cooking oil, preferably castor oil.

[0034] Beneficial effects of the present invention: The monolithic metal fiber @ hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst provided by the present invention has a three-dimensional pore structure, low pressure drop, good thermal conductivity, and good flow diffusion. The hollow multi-level pore structure can reduce the internal diffusion resistance of the catalytic reaction process, significantly improve the catalytic efficiency and selectivity of the catalyst, and effectively inhibit carbon deposition; when used in the gas-phase catalytic cracking reaction of oils and fats, the oils and fats can be completely cracked and fully deoxygenated, and the liquid product yield is above 60%, and its hydrocarbon content can reach 98%, and the aromatic content is as high as 89%. After being recycled for 4 times, the total hydrocarbon content is above 81%. The oil and fat raw materials are widely available, the equipment is simple, the operation is flexible, the adaptability is strong, and the production cost is low. Therefore, the application of the monolithic metal fiber @ hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst and oil and fat catalytic cracking described in the present invention is of great significance for alleviating the energy crisis and developing new energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is the adsorption-desorption isotherm curve and pore size distribution diagram of the monolithic SS-fiber@ hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst prepared in Example 1;

[0036] Figure 2 is the XRD spectrum of the monolithic SS-fiber@ hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst prepared in Example 1;

[0037] Figure 3 is a scanning electron microscope photograph of the monolithic Ti-fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst prepared in Example 2;

[0038] Figure 4 is a transmission electron microscope photograph of the monolithic Ti-fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst prepared in Example 2;

[0039] Figure 5 This is a transmission electron microscope photo of the monolithic SS-fiber@ microporous HZSM-5 molecular sieve core-shell structure catalyst prepared in Comparative Example 1;

[0040] Figure 6 The adsorption-desorption isotherm curve and pore size distribution diagram of the monolithic SS-fiber@microporous HZSM-5 molecular sieve core-shell structure catalyst prepared in comparative example 1;

[0041] Figure 7 This is a transmission electron microscope photo of the monolithic SS-fiber@mesoporous HZSM-5 molecular sieve core-shell structure catalyst prepared in Comparative Example 2;

[0042] Figure 8The adsorption-desorption isotherm curve and pore size distribution diagram of the monolithic SS-fiber@mesoporous HZSM-5 molecular sieve core-shell structure catalyst prepared in comparative example 2;

[0043] Fig. 9 The effect of silicon-aluminum ratio on product yield in the catalytic cracking reaction of castor oil in Application Example 1;

[0044] Fig.10 Application Example 1 is the effect of silicon-aluminum ratio on the composition distribution of liquid products in the catalytic cracking reaction of castor oil;

[0045] Fig.11 The effect of alkali treatment concentration on product yield in castor oil catalytic cracking reaction in Application Example 1;

[0046] Fig.12 Application Example 1 is the effect of alkali treatment concentration on the composition distribution of liquid products in castor oil catalytic cracking reaction;

[0047] Fig.13 This is a graph showing the yield of liquid products in different oil catalytic cracking reactions in Application Example 2;

[0048] Fig.14 It is the composition distribution of liquid products in the catalytic cracking reaction of different oils and fats in Application Example 2;

[0049] Fig.15 It is a comparison chart of the yield of liquid products of the catalysts prepared by Example 1, Comparative Example 1 and Comparative Example 2 in the catalytic cracking reaction of castor oil;

[0050] Fig.16 It is a comparative diagram of the composition distribution of liquid products of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 in the catalytic cracking reaction of castor oil;

[0051] Fig.17 It is the thermogravimetric diagram of carbon deposition of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 after cracking reaction;

[0052] Fig.18 This is a distribution diagram of liquid product composition of the catalyst prepared in Comparative Example 2 in 4 regeneration cycles of catalytic cracking reactions;

[0053] Fig.19 This is a distribution diagram of the liquid product composition of the catalyst prepared in Example 1 in catalytic cracking reactions of four regeneration cycles. DETAILED DESCRIPTION

[0054] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the technical solution of the present invention is further explained below in conjunction with specific embodiments and drawings:

[0055] Example 1

[0056] The preparation method of the monolithic SS-fiber@ hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst in this embodiment is as follows:

[0057] 1. Weigh 2g of nano-pure silicon molecular sieve seed crystals, add them into a beaker containing 98g of deionized water, and stir to mix thoroughly; add ammonia water dropwise to adjust the pH value of the suspension to 10, so as to obtain a suspension containing 2wt% of nano-pure silicon molecular sieve seed crystals.

[0058] 2. Weigh about 4 g of stainless steel fiber sheet (fiber diameter 20 μm, abbreviated as SS-fiber) as a substrate, first place it in acetone for ultrasonication for 5 minutes, take it out and dry it at 100°C, and calcine it at 300°C for 2 hours; then immerse the SS-fiber in the prepared suspension containing 2 wt% of nano-pure silicon molecular sieve seeds, take it out after ultrasonication for about 15 minutes, and dry it in an oven at 100°C overnight to obtain a monolithic SS-fiber substrate pre-coated with nano-pure silicon molecular sieve seeds.

[0059] 3. Place the pre-coated nano-pure silicon molecular sieve seed monolithic SS-fiber substrate prepared in step 2 into a hydrothermal crystallization reactor lined with polytetrafluoroethylene, and add tetraethyl orthosilicate (TEOS), tetrapropylammonium hydroxide (TPAOH), sodium hydroxide (NaOH), aluminum nitrate nonahydrate

[0060] [Al(NO 3 ) 3 9H 2 O] and deionized water in the following molar ratios: TEOS:TPAOH:NaOH:[Al(NO 3 ) 3 9H 2 O]:H 2 O=130:14:13:

[0061] 1.3:2850 was added to 70 mL of crystallization solution (theoretical silicon-aluminum ratio is 100), the kettle was sealed and placed in a 170°C oven for static crystallization for 48 hours. The hydrothermal crystallization can be repeated multiple times to ensure that the molecular sieve loading reaches more than 15%. After washing, drying and calcining at 550°C for 6 hours, the assembled SS-fiber@ZSM-5 was obtained.

[0062] 4. Each 1g of monolithic SS-fiber@ZSM-5 was hydrothermally treated with 5mL of 1mol / L TPAOH solution at 170°C for 24h. After being taken out, it was washed, dried, and calcined at 550°C for 6h to obtain a Na-type monolithic molecular sieve composite.

[0063] 5. The Na-type monolithic molecular sieve complex obtained in step 4 was heated to 1 mol / L NH 4After ion exchange at 80 °C for 6 h (NH 4 Cl solution), washed, dried at 100°C for 1h, and then calcined at 550°C in air for 6h. Finally, the monolithic SS-fiber@ hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst was obtained.

[0064] Weighing revealed that in the integrated SS-fiber@ hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst, the mass percentage of the HZSM-5 molecular sieve layer is 15%, and the mass percentage of the stainless steel fiber matrix is ​​85%. According to ICP testing, the actual silicon-aluminum ratio of the HZSM-5 molecular sieve layer is 108.

[0065] Figure 1 The nitrogen adsorption and desorption isotherm of the monolithic SS-fiber@ hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst prepared in this embodiment is a type IV isotherm. The pore size distribution diagram has obvious mesopores and a specific surface area of ​​83.2 m 2 / g, and the average pore size is 3.5nm. The catalyst contains hollow macropores, mesopores and micropores of the molecular sieve itself, so it belongs to the hollow multi-level pore HZSM-5 molecular sieve.

[0066] Figure 2 This is the XRD spectrum of the monolithic SS-fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst prepared in Example 1. The SS-fiber diffraction peak and the HZSM-5 molecular sieve diffraction peak coexist.

[0067] The silicon-aluminum ratio in step 3 of this embodiment can be adjusted by changing the Al(NO 3 ) 3 9H 2 The amount of O was adjusted to prepare monolithic SS-fiber@ hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalysts with different silicon-aluminum ratios (silicon-aluminum ratio of 50 and 200). The rest was the same as in this example.

[0068] By changing the concentration of TPAOH, the monolithic SS-fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst with different hollow pore diameters was obtained. The concentration of TPAOH solution in step 4 of Example 1 was adjusted to 0.5 mol / L and 2 mol / L respectively, and the rest was the same as Example 2.

[0069] Example 2

[0070] The preparation method of the monolithic stainless steel titanium fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst in this embodiment is as follows:

[0071] 1. Weigh 3g of nano-pure silicon molecular sieve seed crystals, add them into a beaker containing 97g of deionized water, and stir to mix thoroughly; adjust the pH to about 10 with ammonia water to obtain a suspension containing 3wt% of nano-pure silicon molecular sieve seed crystals.

[0072] 2. Prepare a sodium hydroxide solution with a concentration of about 1 mol / L, put about 4 g of titanium fiber (abbreviated as Ti-fiber) into the solution for 5 minutes, wash and dry it, then immerse it in acetone, ultrasonically treat it for 30 minutes, repeatedly wash it with deionized water, dry it in an oven at 100°C, and calcine it at 400°C for 2 hours; then immerse the Ti-fiber in the suspension containing 3 wt% of nano-pure silicon molecular sieve seeds, and ultrasonically vibrate it for about 15 minutes.

[0073] The obtained titanium fiber was then taken out and dried in an oven at 100° C. overnight to obtain a monolithic titanium fiber Ti-fiber substrate pre-coated with nano-pure silicon molecular sieve crystal seeds.

[0074] 3. Place the pre-coated nano-pure silicon molecular sieve seed monolithic Ti-fiber substrate prepared in step 2 into a hydrothermal crystallization reactor, and add tetraethyl orthosilicate (TEOS), tetrapropylammonium hydroxide (TPAOH), sodium hydroxide (NaOH), aluminum nitrate nonahydrate [Al(NO 3 ) 3 9H 2 O] and deionized water in the following molar ratios: TEOS:TPAOH:NaOH:[Al(NO 3 ) 3 9H 2 O]:H 2 O=130:14:13:1.3:2850 in 70mL crystallization solution (theoretical silicon aluminum ratio is 100), sealed and placed in a 180℃ oven for static crystallization for 48h. Hydrothermal crystallization can be performed multiple times to ensure that the molecular sieve loading reaches more than 10%, washed, dried and calcined at 550℃ for 6h to obtain monolithic Ti-fiber@ZSM-5.

[0075] 4. Every 1g of monolithic Ti-fiber@ZSM-5 was hydrothermally treated with 5mL of 1mol / L TPAOH solution at 170°C for 24h. After being taken out, it was washed, dried, and calcined at 550°C for 6h to obtain a Na-type monolithic molecular sieve composite.

[0076] 5. The Na-type monolithic molecular sieve composite obtained in step 4 was heated at 80°C (water bath heating) in 1 mol / L NH 4 After ion exchange in Cl solution for 6 h (NH 4Cl solution), washed, dried at 100°C for 1 hour, and then calcined at 550°C in air atmosphere for 6 hours. The monolithic stainless steel titanium fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst of the present invention is obtained.

[0077] Weighing revealed that the mass percentage of the ZSM-5 molecular sieve layer in the monolithic Ti-fiber@hollow multi-level pore HZSM-5 core-shell structure catalyst was 10.4%, and the mass percentage of the Ti-fiber matrix was 89.6%. According to ICP testing, the actual silicon-aluminum ratio of the HZSM-5 molecular sieve layer was 112.

[0078] Figure 3 and Figure 4 They are scanning electron microscope photos and transmission electron microscope photos of the monolithic Ti-fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst. The molecular sieve forms a hollow mesoporous structure with an internal cavity diameter of about 97nm.

[0079] The composition of the crystallization solution in step 3 of this embodiment can be changed by changing the nonahydrate aluminum nitrate [Al(NO 3 ) 3 9H 2 O] was added to adjust the amount of HZSM-5 molecular sieve shells with different silicon-aluminum ratios, and the rest was the same as in this embodiment.

[0080] Comparative Example 1

[0081] The preparation method of the monolithic SS-fiber@ microporous HZSM-5 molecular sieve core-shell structure catalyst is as follows:

[0082] 1. Weigh 2g of nano-pure silicon molecular sieve seed crystals, add them into a beaker containing 98g of deionized water, and stir to mix thoroughly; add ammonia water dropwise to adjust the pH value of the suspension to 10, so as to obtain a suspension containing 2wt% of nano-pure silicon molecular sieve seed crystals.

[0083] 2. Weigh about 4 g of stainless steel fiber sheet (fiber diameter 20 μm, abbreviated as SS-fiber) as a substrate, first place it in acetone for ultrasonication for 5 minutes, take it out and dry it at 100°C, and calcine it at 300°C for 2 hours; then immerse the SS-fiber in the prepared suspension containing 2 wt% of nano-pure silicon molecular sieve seeds, take it out after ultrasonication for about 15 minutes, and dry it in an oven at 100°C overnight to obtain a monolithic SS-fiber substrate pre-coated with nano-pure silicon molecular sieve seeds.

[0084] 3. The pre-coated nano-pure silicon molecular sieve seed monolithic SS-fiber substrate prepared in step 2 is placed in a hydrothermal crystallization reactor lined with polytetrafluoroethylene, and tetraethyl orthosilicate (TEOS), tetrapropylammonium hydroxide (TPAOH), aluminum nitrate nonahydrate [Al(NO 3 ) 3 9H 2 O] and deionized water in the following molar ratio, TEOS:TPAOH:[Al(NO 3 ) 3 9H 2 O]:H 2 O=130:14:1.3:2850 in 70mL crystallization solution (theoretical silicon aluminum ratio is 100), sealed the kettle and placed in a 170℃ oven for static crystallization for 48h. Hydrothermal crystallization can be performed multiple times to ensure that the molecular sieve loading reaches more than 15%, washed, dried and calcined at 550℃ for 6h to obtain the monolithic SS-fiber@ZSM-5.

[0085] 4. The catalyst obtained in step 3 was heated to 1 mol / L NH 4 After ion exchange at 80 °C for 6 h (NH 4 Cl solution), washed, dried at 100℃ for 1h, and then calcined at 550℃ in air atmosphere for 6h. Finally, the monolithic SS-fiber@ microporous HZSM-5 molecular sieve core-shell structure catalyst was obtained. According to ICP test, the actual silicon-aluminum ratio of the HZSM-5 molecular sieve layer is 102.

[0086] It was found by weighing that the mass percentage of the HZSM-5 molecular sieve layer in the monolithic SS-fiber@ microporous HZSM-5 molecular sieve core-shell structure catalyst was 16.3%.

[0087] Figure 5 This is a transmission electron microscope photo of the monolithic SS-fiber@ microporous HZSM-5 molecular sieve core-shell structure catalyst. ZSM-5 is a solid coffin-shaped crystal without hollow and mesoporous structure.

[0088] Figure 6 This is the nitrogen adsorption and desorption isotherm of the monolithic SS-fiber@microporous HZSM-5 molecular sieve core-shell structure catalyst. It shows a small hysteresis loop and a specific surface area of ​​48.4m 2 / g, and the average pore size is 2.3nm, which is significantly lower than the specific surface area and pore size of Example 1. The catalyst was not added with NaOH during hydrothermal crystallization, nor was it subjected to subsequent alkali treatment, so the pore structure it possessed was only the micropores of the HZSM-5 molecular sieve itself and the mesopores formed by the accumulation of a small part of the molecular sieve crystals.

[0089] Comparative Example 2

[0090] The preparation method of the monolithic SS-fiber@mesoporous HZSM-5 molecular sieve core-shell structure catalyst is as follows:

[0091] 1. Weigh 2g of nano-pure silicon molecular sieve seed crystals, add them into a beaker containing 98g of deionized water, and stir to mix thoroughly; add ammonia water dropwise to adjust the pH value of the suspension to 10, so as to obtain a suspension containing 2wt% of nano-pure silicon molecular sieve seed crystals.

[0092] 2. Weigh about 4 g of stainless steel fiber sheet (fiber diameter 20 μm, abbreviated as SS-fiber) as a substrate, first place it in acetone for ultrasonication for 5 minutes, take it out and dry it at 100°C, and calcine it at 300°C for 2 hours; then immerse the SS-fiber in the prepared suspension containing 2 wt% of nano-pure silicon molecular sieve seeds, take it out after ultrasonication for about 15 minutes, and dry it in an oven at 100°C overnight to obtain a monolithic SS-fiber substrate pre-coated with nano-pure silicon molecular sieve seeds.

[0093] 3. Place the pre-coated nano-pure silicon molecular sieve seed monolithic SS-fiber substrate prepared in step 2 into a hydrothermal crystallization reactor lined with polytetrafluoroethylene, and add tetraethyl orthosilicate (TEOS), tetrapropylammonium hydroxide (TPAOH), sodium hydroxide (NaOH), aluminum nitrate nonahydrate

[0094] [Al(NO 3 ) 3 9H 2 O] and deionized water in the following molar ratios: TEOS:TPAOH:NaOH:[Al(NO 3 ) 3 9H 2 O]:H 2 O=130:14:13:

[0095] 1.3:2850 was added to 70 mL of crystallization solution (theoretical silicon-aluminum ratio is 100), the kettle was sealed and placed in a 170°C oven for static crystallization for 48 hours. The hydrothermal crystallization can be repeated multiple times to ensure that the molecular sieve loading reaches more than 15%. After washing, drying and calcining at 550°C for 6 hours, the assembled SS-fiber@ZSM-5 was obtained.

[0096] 4. The catalyst obtained in step 3 was heated to 1 mol / L NH 4 After ion exchange at 80 °C for 6 h (NH 4Cl solution), washed, dried at 100℃ for 1h, and then calcined at 550℃ in air atmosphere for 6h. Finally, the monolithic SS-fiber@ mesoporous HZSM-5 molecular sieve core-shell structure catalyst was obtained. According to ICP test, the actual silicon-aluminum ratio of the HZSM-5 molecular sieve layer is 106.

[0097] It was found by weighing that the mass percentage of the HZSM-5 molecular sieve layer in the monolithic SS-fiber@mesoporous HZSM-5 molecular sieve core-shell structure catalyst was 16.5%.

[0098] Figure 7 This is a transmission electron microscope photo of the monolithic SS-fiber@mesoporous HZSM-5 molecular sieve core-shell structure catalyst. The addition of sodium hydroxide during hydrothermal synthesis creates a higher alkaline environment, which is conducive to the formation of mesopores in the molecular sieve. Its TEM image shows the pores of its mesopores, but since there is no subsequent alkaline treatment, there is no hollow structure.

[0099] Figure 8 The nitrogen adsorption and desorption isotherm of the monolithic SS-fiber@ mesoporous HZSM-5 molecular sieve core-shell structure catalyst has a type IV isotherm and an H4 hysteresis loop, with a specific surface area of ​​58.1m 2 / g, and the average pore size in its pore size distribution diagram is 3.8nm, indicating that the addition of alkali during the hydrothermal process promotes the formation of mesopores.

[0100] Application Example 1

[0101] The reaction performance of the monolithic SS-fiber@ hollow multi-stage pore HZSM-5 molecular sieve core-shell structure catalyst with different silicon-aluminum ratios and different alkali treatment concentrations prepared in Example 1 in the catalytic cracking reaction of castor oil was investigated in a fixed bed reactor. 6.667g of catalyst was loaded into the cracking tube of the tubular reactor, and nitrogen was introduced to evacuate the air in the reaction tube to avoid the side reaction of oxygen with castor oil under high temperature; the cracking tube was heated by a two-stage tubular heating furnace, the temperature of the first stage was set to 380°C, and the temperature of the second stage was set to 480°C, and castor oil was pumped into the tube at a specific flow rate by a peristaltic pump. After preheating and gasification, the castor oil gas passed through the catalyst and cracking reaction occurred; the gaseous and liquid products were collected by a gas collection device and a liquid collection device respectively, and GC-MS analysis was performed on them.

[0102] The yield of liquid product is calculated as follows:

[0103] Liquid product yield = mass of liquid product / mass of castor oil × 100%

[0104] Reaction conditions: oil mass space velocity is 4h -1, nitrogen flow rate is 20mL / min, reaction temperature is 480℃. The effect of silicon-aluminum ratio on product yield and liquid product composition distribution is investigated under the above conditions. Fig. 9 and Fig.10 The reaction performance of the monolithic SS-fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst with different silicon-aluminum ratios in the catalytic cracking reaction of castor oil is shown in Table 1.

[0105] Table 1. Effect of different silicon-aluminum ratios on the composition distribution of liquid products

[0106]

[0107] The silicon-aluminum ratio has little effect on the liquid phase yield of the product, but has a significant effect on the distribution of the liquid product. When Si / Al is 100, the content of hydrocarbons and aromatics in the liquid product is much better than that of Si / Al of 50 and 200. The monolithic SS-fiber@hollow multi-level pore HZSM-5 molecular sieve catalyst with a silicon-aluminum ratio of 100 has better cracking performance and deoxygenation performance.

[0108] Under the above conditions, the effect of alkali treatment concentration on product yield and liquid product composition distribution was investigated. Fig.11 and Fig.12 The reaction performance of the monolithic SS-fiber@ hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst with different alkali treatment concentrations in the catalytic cracking reaction of castor oil is shown in Table 2. When the yield is not greatly affected, the alkali treatment concentration has a great influence on the composition distribution of the liquid product. Among them, the liquid product obtained by the catalyst treated with 1 mol / L TPAOH has a hydrocarbon content of up to 98.5%, an aromatic content of up to 89.2%, and the cracking and deoxygenation performance is the best.

[0109] Table 2. Effect of different alkali treatment concentrations on the composition distribution of liquid products

[0110]

[0111]

[0112] Application Example 2

[0113] The reaction performance of the monolithic Ti-fiber@ hollow multi-stage pore HZSM-5 core-shell structure catalyst with a silicon-aluminum ratio of 100 prepared in Example 2 in the catalytic cracking reaction of castor oil, palm oil and frying waste oil was investigated in a fixed bed reactor. 9.615g of catalyst was loaded into the cracking tube of the tubular reactor, and nitrogen was introduced to exhaust the air in the reaction tube; the cracking tube was heated by a two-stage tubular heating furnace, the first stage temperature was the oil vaporization temperature, palm oil was set to 400℃, frying oil was set to 330℃, and castor oil was set to 380℃, and the second stage temperature was set according to the specific cracking reaction temperature, palm oil was set to 510℃, frying oil was set to 480℃, and castor oil was set to 500℃; the oil was pumped into the tube at a specific flow rate by a peristaltic pump, preheated and gasified, and then passed through the catalyst and cracking reaction occurred; the gaseous and liquid products were collected by a gas collection device and a liquid collection device respectively, and GC-MS analysis was performed on them.

[0114] The yield of liquid product is calculated as follows:

[0115] Liquid product yield = liquid product mass / oil mass × 100%

[0116] Reaction conditions: nitrogen flow rate is 20 mL min -1 , oil mass air velocity is 4h -1 Under the above conditions, the monolithic Ti-fiber@hollow multi-level pore HZSM-5 catalyst was used to investigate the effects of different bio-oils on the products. The product yield graph and liquid product distribution graph are shown in Fig.13 and 14 The catalytic performance of the catalyst of this embodiment for different oils and fats is shown in Table 3.

[0117] Table 3. Composition distribution of liquid products obtained by catalytic cracking of different oils and fats by catalyst in Example 2

[0118]

[0119] For the three types of oils, the catalyst can achieve ideal results, with ideal liquid product yields and more than 90% hydrocarbon content in the liquid products, indicating that the catalyst has good catalytic cracking and deoxygenation capabilities for different oils. Among them, the aromatic selectivity of catalytic cracking castor oil is better than that of the other two groups of catalysts, and the catalytic performance of the catalyst for castor oil is more superior.

[0120] Comparative application example 1

[0121] The reaction performance of the three catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 in the catalytic cracking reaction of castor oil was investigated in a fixed bed reactor. The catalyst (the mass of the molecular sieve in the catalyst was 1 g) was loaded into the cracking tube of the tubular reactor, and nitrogen was introduced to exhaust the air in the reaction tube; the cracking tube was heated by a two-stage tubular heating furnace, with the temperature of the first stage set to 380°C and the temperature of the second stage set to 480°C; castor oil was pumped into the tube at a specific flow rate by a peristaltic pump, and after preheating and gasification, the castor oil flowed through the catalyst and a cracking reaction occurred; the gaseous and liquid products were collected by a gas collection device and a liquid collection device, respectively, and GC-MS analysis was performed on them.

[0122] The yield of liquid product is calculated as follows:

[0123] Liquid product yield = mass of liquid product / mass of castor oil × 100%

[0124] Reaction conditions: catalyst silicon-aluminum ratio of 100, nitrogen flow rate of 20 mL min -1 , temperature 480℃, mass space velocity 4h -1 Under the above conditions, the effects of different pore sizes in the molecular sieve on the yield of the structured catalyst cracking product and the composition distribution of the liquid product were investigated. Fig.15 and Fig.16 As shown, the reaction performances of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 in the catalytic cracking reaction of castor oil are shown in Table 4.

[0125] Table 4. Reaction performance of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 in the catalytic cracking reaction of castor oil

[0126]

[0127] Although the liquid product yield of the microporous catalyst is high (more than 70%), the cracking and deoxygenation effects are far worse than those of the other two catalysts (the hydrocarbon content is only 42%), indicating that the mesopores play an important role in improving the mass transfer rate and the utilization rate of the acid sites. The presence of only micropores will cause the catalyst to quickly accumulate carbon and deactivate, and lose the cracking and deoxygenation capabilities. Compared with the mesoporous catalyst, the hollow multi-level pore catalyst has a higher hydrocarbon selectivity and contains almost no oxygen-containing compounds such as aldehydes and acids. The hollow mesopores are more conducive to improving the mass transfer rate and the utilization rate of the acid sites.

[0128] The carbon deposition performance of the three catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 is as follows: Fig.17 As shown, it can be seen that the microporous catalyst has the least carbon deposition, but the cracking and deoxidation effects are very poor, indicating that the catalyst has poor carbon tolerance and is easily deactivated by carbon deposition. In contrast, the mesoporous catalyst and hollow multi-level pore catalyst have high carbon tolerance, more exposed active sites and are not easily covered by carbon deposition and deactivated.

[0129] The reusability of the two mesoporous catalysts in Example 1 and Comparative Example 2 (the catalysts are regenerated by high-temperature carbonization and recycled) is as follows: Fig.18 and Fig.19 As shown, the liquid yield of the catalyst of comparative example 2 remains basically unchanged as the number of times of use increases, but the product distribution changes greatly, and the hydrocarbon content decreases gradually. After 4 regenerations, the content of alkanes, alkenes and aromatics drops from 93% to 49%; while the catalyst of example 1 can still maintain 97% hydrocarbon content after 3 regenerations, and the hydrocarbon content drops to 84% after 4 regenerations. This shows that the monolithic SS-fiber@ hollow multi-level pore HZSM-5 catalyst has good reusability and anti-carbon deposition ability.

Claims

1. A monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve catalyst, characterized in that: It consists of a monolithic metal fiber matrix and a ZSM-5 molecular sieve layer with an internal hollow, multi-level pore structure, wherein the monolithic metal fiber matrix is ​​the inner core and the hollow multi-level pore HZSM-5 molecular sieve is the casing, forming a three-dimensional network structure composed of several coaxial casing-type core-shell structures.

2. The monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve structure catalyst as claimed in claim 1, characterized in that: The metal fiber is copper fiber, nickel fiber, stainless steel fiber or titanium fiber, and the diameter of each metal fiber is 2-50 μm. The hollow multi-level pore HZSM-5 molecular sieve is a silicon-aluminum molecular sieve with a Si / Al molar ratio of 20-500 or a pure silicon molecular sieve without aluminum. The mass percentage of the hollow multi-level pore ZSM-5 molecular sieve in the monolithic catalyst is 2-30%. The hollow structure pore diameter of the hollow multi-level pore ZSM-5 molecular sieve is 50-800 nm, and the multi-level pores include macropores, mesopores and micropores. The macropore porosity is 60-95%, and the mesopore diameter is adjustable in the range of 2-50 nm. The micropores come from the ZSM-5 molecular sieve crystal structure, and the micropore diameter is less than 2 nm. The specific surface area is 20-100 m 2 g -1 .

3. The method for preparing the monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst according to claim 1 or 2, characterized in that: The following steps are involved: a) using a monolithic metal fiber sheet as a substrate, firstly performing a surface pretreatment on the monolithic metal fiber sheet, then immersing the monolithic metal fiber sheet in a suspension aqueous solution composed of nano ZSM-5 seed crystals, taking the monolithic metal fiber sheet out and drying it after immersion for a certain period of time, thereby obtaining a monolithic metal fiber substrate pre-coated with nano molecular sieve seed crystals; b) placing the monolithic metal fiber substrate pre-coated with nano ZSM-5 seed crystals into a molecular sieve crystallization solution for hydrothermal crystallization growth, and calcining the obtained structured molecular sieve at a certain temperature for a certain time; c) adding the structured molecular sieve into an alkaline solution for secondary hydrothermal crystallization or water bath stirring; d) The prepared structured hollow multi-level pore molecular sieve is subjected to ion exchange with NH4Cl solution to obtain an H-type molecular sieve, which is then calcined.

4. The method for preparing the monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst according to claim 3, characterized in that: In the step a), the surface pretreatment of the monolithic metal fiber matrix is ​​performed as follows: the monolithic metal fiber sheet is placed in acetone, ultrasonicated for 5 to 30 minutes, placed in a 40 to 100 ° C oven for drying, and calcined at 200 to 500 ° C for 1 to 5 hours; in the suspended aqueous solution in the step a), the mass percentage of the nano ZSM-5 seeds is 1% to 5%, the nano ZSM-5 seeds are pure silicon molecular sieves or silicon aluminum molecular sieves with a Si / Al molar ratio of 20 to 500, the immersion time is 2 to 24 hours, and the drying conditions are 100 ° C for 6 to 12 hours.

5. The method for preparing the monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst according to claim 3, characterized in that: In the step b), the molecular sieve crystallization liquid is prepared from tetraethyl orthosilicate (TEOS), tetrapropylammonium hydroxide (TPAOH), aluminum nitrate nonahydrate [Al(NO3)3·9H2O], sodium hydroxide (NaOH) and deionized water in a molar ratio of TEOS: TPAOH: [Al(NO3)3·9H2O]: NaOH: H2O = 130: (14~50): (0.5~5): (5~13): (20~1000).

6. The method for preparing the monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst according to claim 3, characterized in that: The conditions for hydrothermal crystallization growth in step b) and step c) are as follows: static crystallization at 90-180° C. for 6-72 h, and the conditions for calcination in step b) and step d) are as follows: calcination in air atmosphere at 500-600° C. for 5-6 h.

7. The method for preparing the monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst according to claim 3, characterized in that: In the step c), the concentration of the alkaline solution is 0.01-2 mol / L, and the heating and stirring conditions are 20-80° C. and stirred for 10-120 min. The composition of the alkaline solution includes one or more of NaOH, TPAOH, NaHCO 3 , and Na 2 CO 3 .

8. The method for preparing the monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst according to claim 3, characterized in that: The conditions of ion exchange in step d) are as follows: ion exchange at 60-90° C. for 1-12 h, and the concentration of NH 4 Cl solution is 0.1-2 mol / L.

9. Application of the monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst in gas phase catalytic cracking of vegetable oil or waste oil as claimed in claim 1 or 2, characterized in that: The monolithic metal fiber@hollow multi-level pore HZSM-5 molecular sieve core-shell structure catalyst is used as a catalyst in the gas phase catalytic cracking process of vegetable oil or waste oil, and has good aromatic selectivity and anti-carbon deposition performance. The method is as follows: a) The monolithic metal fiber@hollow multi-level pore HZSM-5 core-shell structure catalyst is loaded into the quartz tube of the tubular reactor, and the mass of the molecular sieve in the catalyst is 1g; nitrogen gas with a certain flow rate is continuously introduced into the tube as a carrier gas to avoid the side reaction of oxygen with oil under high temperature; b) Use a two-stage tubular heating furnace to heat the quartz cracking tube. The temperature of the first stage is set at 300~450℃ to fully preheat and gasify the oil; the temperature of the second stage is set according to the specific reaction temperature, ranging from 380~550℃; c) The oil enters the quartz cracking tube at a certain flow rate through a peristaltic pump, and after preheating and vaporization, a continuous catalytic cracking reaction occurs; the mass space velocity of the oil is 1~15 h -1 , the gaseous and liquid products are collected by a gas collecting device and a liquid collecting device respectively for analysis.

10. The use according to claim 9, characterized in that: The catalyst silicon-aluminum ratio was 100 and the nitrogen flow rate was 20 mL min -1 The mass space velocity of oil is 4 h -1 The yield of liquid products is over 60%, among which the hydrocarbon content in the liquid products is as high as 98% and the aromatic content is as high as 89%.